1986
DOI: 10.1161/01.res.58.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic beta 2-adrenoceptor control of renal sympathetic nerve activity and urinary sodium excretion in conscious, spontaneously hypertensive rats.

Abstract: SUMMARY. The contributions of /Si-, B^-, and a 2 -adrenoceptors in the posterior hypothalamus to the increased renal sympathetic nerve activity and decreased urinary sodium excretion resulting from environmental stress (air jet) in conscious spontaneously hypertensive rats were examined. Air stress increased mean arterial pressure and renal sympathetic nerve activity (54% from 7.0 ± 0.7 integrator resets/min), and decreased urinary sodium excretion (44% from 2.7 ± 0.4 ^Eq/min per 100 g body weight). After bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…For example, we have demonstrated that sympathetic presynaptic ␤ 2 -adrenoceptor-mediated facilitation of neurogenic pressor response in mesenteric arteries is enhanced in 4-wk-old prehypertensive SHR (52). Also, ␤ 2 -adrenoceptors in the posterior hypothalamus are actively involved in mediating the increased renal sympathetic nerve activity and antinatriuresis resulting from environmental stress in maintaining hypertension in 16wk-old conscious SHR (25). These results suggest that the blunted responses in hypertensive animals are not likely due to dysfunction of ␤ 2 -adrenoceptors on nitrergic nerve terminals.…”
Section: Discussionmentioning
confidence: 90%
“…For example, we have demonstrated that sympathetic presynaptic ␤ 2 -adrenoceptor-mediated facilitation of neurogenic pressor response in mesenteric arteries is enhanced in 4-wk-old prehypertensive SHR (52). Also, ␤ 2 -adrenoceptors in the posterior hypothalamus are actively involved in mediating the increased renal sympathetic nerve activity and antinatriuresis resulting from environmental stress in maintaining hypertension in 16wk-old conscious SHR (25). These results suggest that the blunted responses in hypertensive animals are not likely due to dysfunction of ␤ 2 -adrenoceptors on nitrergic nerve terminals.…”
Section: Discussionmentioning
confidence: 90%
“…It must be neu ronal, since there is some information to support this hypothesis. For instance, electrophysiological studies have suggested that hypothalamic nuclei neuronally influence the kidney to increase reabsorption of water (30,31). Koepke et al (31) suggest that the antidiuretic effect of a (32-agonist injected into the posterior hypothalamus was due to increased activity of renal sympathetic neu rons.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral ß-adrenoceptors are involved in several physiological functions, such as respiratory [12,81], cardiovascular [231] and renal [132] sympathetic nervous control. Furthermore, ß-adrenoceptors located on glial cells regulate (injuryinduced) astrogliosis and microglial proliferation [224,85,104,83].…”
Section: Introductionmentioning
confidence: 99%